The Representation of Women in Instant Seasoning Advertisements - Widi Astuti Winara (Passage, 2015)
This study entitled The Representation of Women in Instant Seasoning Advertisements. This study aims to investigate how women are represented in instant seasoning advertisements and reveal ideologies behind the representation. This study investigates the representation of women in five instant seasoning advertisements; ABC ‘Sambal Masak’ advertisement “Kayak Masakan Mami”, Royco ‘All in One’ advertisement “Ini Resepku”, Indofood ‘Bumbu Racik Tempe’ advertisement “Resep Kering Tempe”, Masako ‘Bumbu Kaldu Penyedap’ advertisement “Cuma Ubi”, and ‘Bango ‘Bumbu Ayam Goreng Bacem’ advertisement “Petani Ketumbar”. The advertisements were downloaded randomly from www.youtube.com. This study uses a descriptive qualitative method. Women in instant seasoning advertisements were investigated through the visual elements of the advertisements as follows; actresses (physical appearance, fashion, facial expression and emotion), setting and properties, frame size, camera angle, and color saturation. This study uses order of signification’s theory by Barthes (1957), reading images’ theory by Kress and Leuween (2006), and some theories of visual elements in television advertisement. The results show that women are mostly represented as brave, feminine, motherly, cheerful, independent, calm, optimistic, and modern women. The study also concludes that there are three ideologies in instant seasoning advertisements: femininity, modernism, and recreation.Keywords: Semiotics, Representation, Women, Advertisements